Impactos do Crédito Rural na produtividade da terra e do trabalho nas regiões brasileiras - SANTOS, Ricardo Bruno Nascimento dos (2015)
The objective of this paper is to measure the impacts of farm credit on the productivity of the land and labor in Brazilian regions. The methodological approach is based on credit constraint model and propensity score matching. Micro data from the 2006 agricultural census are used. Results show that credit is not effective to improve the productivity of the factors in agricultural sector, except in the Northeast region. Finally, these results emphasize the need of improvements in farm credit policy of Brazil.